EVALUASI PROGRAM PENGABDIAN KEPADA MASYARAKAT SKEMA PMP BERBASIS MODEL CIPP - Ramdhani, Luthfi Ilham; Badrujaman, Aip; Madani, Faisal; Priyanto, Sugeng (Jurnal Administrasi Pendidikan Indonesia, 2024)
Although the implementation of the Community Service Program (PMP) in higher education demonstrates high participation and funding distribution, its effectiveness in supporting the achievement of the Tri Dharma of Higher Education objectives has not been comprehensively evaluated. Therefore, a comprehensive evaluation of the program's implementation is needed. Therefore, this study aims to evaluate the 2023 Beginner Community Empowerment Program (PMP) organized by the Directorate of Research, Technology, and Community Service (DRTPM) of the Ministry of Education, Culture, Research, and Technology, using the CIPP (Context, Input, Process, Product) evaluation model. The primary focus is directed at the Product aspect, taking into account the systemic interconnectedness of all model components. Secondary data were obtained from 487 output validation documents and 105 national monitoring reports. In contrast, primary data were collected through in-depth interviews with three key informants who are national reviewers and program guideline compilers. The evaluation results show that the quantitative achievement of five types of outputs (scientific articles, popular articles/mass media, videos, posters, and partner empowerment) is relatively high. However, the quality of the substance and partner participation still varies. The main weaknesses lie in the program planning stage, the lack of data-based needs assessments, and the minimal involvement of partners as co-creators. These findings underscore the importance of revising implementation guidelines, strengthening implementers' technical capacity, and validating quality-based outcomes. The CIPP model has proven effective in identifying root causes and providing direction for systemic and sustainable program improvement.